2007
DOI: 10.1111/j.1478-3231.2007.01632.x
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones are associated with carotid atherosclerosis

Abstract: Subjects with GD exhibit greater carotid atherosclerosis, and therefore have a higher risk for stroke and myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
1
13
0
2
Order By: Relevance
“…Significant associations between gallstone disease and CHD risk were also observed in cross-sectional studies, 19, 20 and other prospective cohort studies in Asian 21, 22 and German 17 populations. The most recent and largest prospective study so far emerged from the China Kadoorie Biobank study, 22 which involved 199,292 men and 288,081 women, followed for a median 7.2 years.…”
Section: Discussionsupporting
confidence: 54%
“…Significant associations between gallstone disease and CHD risk were also observed in cross-sectional studies, 19, 20 and other prospective cohort studies in Asian 21, 22 and German 17 populations. The most recent and largest prospective study so far emerged from the China Kadoorie Biobank study, 22 which involved 199,292 men and 288,081 women, followed for a median 7.2 years.…”
Section: Discussionsupporting
confidence: 54%
“…In those studies, patients were not limited to CAD. More recently, two studies reported that cardiovascular disease, defined by ultrasonographic measurements of carotid artery intima-media thickness [13], and coronary heart disease, defined as myocardial ischemia using the excise treadmill test based on the Bruce protocol [20], were associated with gallstone disease. These diagnostic criteria, however, have several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Gallstone disease was confirmed by B-type ultrasonography, using the same criteria as reported [13]. Patients with previous cholecystectomies were not included because of uncertainty whether their indications for surgery were gallstone disease or other gallbladder diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Recently Mendez-Sanchez et al26) reported that carotid IMT increased in gallstone patients and a 0.1 mm increase in carotid IMT increased the prevalence of gallstone disease by 1.25 times (95% CI, 1.02 to 1.53; P = 0.027). Also Mendez-Sanchez et al27) reported that patients with coronary artery disease were at higher risk for gallstone disease (odds ratio, 2.84), and Chavez-Tapia et al28) reported that patients undergoing cholecystectomy were at greater risk for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 96%